Можливість виявлення потенційно ненадійних елементів електроніки - Колодій, З. О.; Крук, О. Г.; Kolodiy, Z.; Kruk, O. (Видавництво Львівської політехніки, 2018)
Наведено результати комп’ютерного моделювання власного шуму елемента електроніки (ЕЕ) для різних моделей його внутрішньої структури. Наведено результати експериментальних досліджень власного шуму ЕЕ в діапазоні низьких частот, які підтверджують результати комп’ютерного моделювання, а саме: вищий рівень шуму в діапазоні низьких частот мають ті ЕЕ, у внутрішній структурі яких більше дефектів. Наведено аналітичний вираз енергетичного спектра власного шуму ЕЕ, у якому параметр τ залежить від особливостей внутрішньої структури ЕЕ. Показано, що виявлення потенційно ненадійних елементів можна здійснювати або за рівнем їхнього власного шуму в діапазоні низьких частот, або за значенням параметра τ.

Hidden defects can turn into obvious defects and characteristics of electronic elements become inappropriate. Therefore, the techniques of non-destructive diagnostics of inner structure state are of great importance. One of these techniques is the diagnostics of electronics by their own noise, which advantageously differs by low time consuming and absence of the risk of damage of the element under investigation. Noise measurements are capable to detect the defects in a material with a sensitivity that cannot be reached by other methods. The results of computer simulation of noise for different models of its internal structure are presented. The simulation was carried out in order to reveal the influence of the internal structure elements of the system under study on the level of its noise at low frequency range. It is shown that systems with fewer structural elements have lower noise level at low frequencies concerning the systems that comprise more elements. The results of the simulation also demonstrate that systems with the same number of structure elements are inherent in different noise levels in low frequency range: systems with an ordered arrangement of the elements are the less noisy then more disordered omes. The results of noise studies of metal films, composite resistors and semiconductor diodes at low-frequency range are presented. It is noted that noise of composite resistors at low frequencies is greater than noise of the metal film resistors for the same scattering power (0,125 watts). The noise of the diodes at low frequencies is much larger than the resistors noise. The increase in noise for diodes can be explained within the hypothesis of the substantial influence of the internal structure of the test sample. Analytical expression of the energy spectrum of the own noise of electronic element, which parameter τ depends on the features of the internal structure, is presented. It has been shown that the detection of potentially unreliable elements can be carried out either by the level of their own noise at the low-frequency band or by the value of the parameter τ.
Ability of identifying the unreliable elements of electronics
Keywords: флікер-шум; внутрішня структура; енергетичний спектр; час релаксації; Flicker Noise; Inner Structure; Energy Spectrum; Relaxation Time